A Critical Appraisal on the Role of Varicocele in Male Infertility - Ricardo Miyaoka; Sandro C. Esteves (Advances in Urology)
Varicocele is a major cause of male infertility, as it may impair spermatogenesis through several distinct physiopathological mechanisms. With the recent advances in biomolecular techniques and the development of novel sperm functional tests, it has been possible to better understand the mechanisms involved in testicular damage provoked by varicocele and, therefore, propose optimized ways to prevent and/or reverse them. Up to now, there is still controversy involving the true benefit of varicocele repair in subfertile men as well as in certain specific situations such as concomitant contralateral subclinical varicocele or associated nonobstructive azoospermia. Also, with the continued development of assisted reproductive technology new issues and questions are emerging regarding the role of varicocelectomy in this context. This paper reviews the most recent data available on the pathogenesis, diagnosis, and management of varicocele with regard to male infertility.